Pengembangan Sistem Aplikasi Barbershop Berbasis Android untuk Meningkatkan Efisiensi dan Efektivitas Pelayanan di Barbershop - Fiqih Refwahajan; Anita Fira Waluyo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2024)
Barbershop is an innovation or development from a men's haircut to a special men's grooming place for hair. Barbershop not only provides haircut services, but many other services are presented such as shaving, coloring, etc. At this time, service order submissions are still made through the WhatsApp platform or telephone or come directly to the Barbershop and queue so that customers feel less satisfied because sometimes it is necessary to wait a long time. To solve this problem, a Barbershop service application was created that customers can use to order services and then Barbershop managers can manage these services only through the application. The application is built using the Flutter and PHP programming languages, is supported by the Laravel framework, and relies on the MySQL database management system to make database management easier. Some of the features provided by the application include booking services, choosing a barberman, and choosing a service time. Thus, this application can help services in Barbershop become more effective and efficient.